Discourse of Substitute Heirs in the Indonesian Heritage Legal Practice: Comparative Perspective - Nawir Yuslem; Mhd. Yadi Harahap; Suarni Suarni (Justicia Islamica, 2021)
This article examines substitute heirs in Islamic and civil code inheritance laws. In Islamic inheritance law, substitute heirs are regulated based on the provisions of the Islamic Law Compilation in Article 185, stating that if the heirs die, their inheritance rights are given to their children. In the civil code, substitute heirs are regulated based on articles 841-848, with provisions covering the replacement of rights and obligations such as the replaced person’s life. This research relies on two questions: what are the substitute heir concepts according to Islamic and civil code inheritance laws? Moreover, how is the comparison of substitute heir concepts based on Islamic and civil code inheritance laws? This study aims to analyze the existence of substitute heirs in Islamic and civil code inheritance laws. To answer both questions, this research employed a normative juridical method, with an approach to laws, cases, comparisons, and conceptual approaches, including conceptual theories and ideas regarding the substitute heir concept from the perspective of Islamic and civil code inheritance laws. This study finds that Islamic inheritance law is based on the Qur’an and hadith, mentioning that the share of the substitute heirs is not the same as that of the replaced heirs. In contrast, according to civil law, the share of the substitute heirs is similar to that of the replaced heirs. Furthermore, this study contributes significantly to realizing benefit, peace, and justice in the distribution of inheritance.